(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective: this study aimed to identify a stroke prevention model with a family approach. Methods: this systematic review is based on the 2015 Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guideline. Articles were obtained from the PubMed and Google Scholar databases. Each article was assessed using eight criteria from the Strengthening the Reporting of Observational studies in Epidemiology (STROBE): sample size, sampling technique, response rate, outcome measures, statistical analysis, use of confounding, study limitations, and ethical considerations. 8 out of 2065 articles were used to develop this study. Results: family support plays an important role in shaping stroke prevention behavior, both primary and secondary, through risk factor management and knowledge provision. Conclusions: family support is one of the approaches to stroke prevention in reducing the burden of stroke. Stroke prevention by the family can be achieved by educating patients about stroke and providing support and encouragement for risk factor management.